Carbon dioxide mineralization for the disposition of blast‐furnace slag: reaction intensification using NaCl solutions. Issue 2 (25th December 2018) - Ren, Enze; Tang, Siyang; Liu, Changjun; Yue, Hairong; Li, Chun; Liang, Bin
Abstract: Carbon dioxide mineralization for the disposition of blast‐furnace slag is an important method for reducing CO2 emissions and simultaneously dealing with solid waste from the steel industry. However, due to the stable structures and properties of blast‐furnace slag, low mineralization reaction efficiency is a key issue in this process and hinders industrial applications. This work presents a method for enhancing the CO2 mineralization reaction by the addition of salt solutions (e.g., NaCl 1 mol · L −1 ) in the slurry of the blast‐furnace slag (<75 μm). The results showed that CO2 mineralization efficiency could be greatly improved with a high CO2 storage amount of ∼280 kg CO 2 · tBFS −1 at a liquid‐solid ratio (L/S ratio) of 10, a temperature of 150°C and CO2 pressure of 3 MPa. The mineralization process was systematically characterized to identify the mechanism for mineralization enhancement by saline solution. The results indicated that saline solution could accelerate the dissolution of Ca 2+ in blast‐furnace slag, reduce the activity of water, and lead to high acidity in the solution, and thus facilitate mineralization and improve the reaction rate. The NaCl solution was not consumed and could be recycled in the process, suggesting that this approach could use the brine and saline water as the medium for solid waste treatment and CO2 emission reduction in high energy‐consuming industries such as mineral processing, power plants, and the steel industry. © 2018 Society of Chemical Industry and John Wiley & Sons, Ltd.